Ḍawābiṭ Ma‘rifah al-Waḍ‘u fī Matan al-Ḥadīth al-Nabawī (al-Manār al-Munīf li Ibn Qayyīm al-Jawziyyah Namūdhajan) - â€˜Abd AllÄá¸¥, IsmÄâ€˜Ä«l; â€˜Abd al-ManÄá¹£, SayÅ«á¹Ä« (Jurnal Usuluddin, 2004)
Hadith mawdu (fabricated hadith) is categorized as the worst type of hadith daif (weak hadith) and hence is listed at the lowest rant It is considered disastrous as it may cause the emergence of superstitious belief, deviation, misconception, and deception against the Prophet (p.b.u.h). The fabricated hadith may occurs both in the textual aspect and in the narration. Ibn Qayyim al-Jawziyah was among the prominent scholars who focused his study solely on the textual aspect. This article tries to highlight the occurance of fabrication in the text (matn) of ahadith and the methodologies designated by Ibn Qayyim to detect this forgery.